mRNA m 6 A modifications and the RNA-binding protein YTHDF1 affect translational control in both normal and pathological learning - Zhuoyue Shi; Kailong Wen; Wenqin Fu; Zhongyu Zou; Kathryn Guo; Nabilah H. Sammudin; Meera J. Patel; Xiangbin Ruan; Shivang Sullere; Shuai Wang; Xiaochang Zhang; Gopal Thinakaran; et al. (Proceedings of the National Academy of Sciences, 2026)
Animals learn and adapt to environmental changes. However, neural plasticity can also become maladaptive, leading to neurological and psychiatric disorders. How do we use known molecular mechanisms to harness the power of neural plasticity to prevent and treat diseases? Consolidating learning is known to require new protein synthesis. We found that mRNA m 6 A modifications and the RNA-binding protein YTHDF1 are required for molecular, cellular, and behavioral adaptations in response to environmental changes. Deletion of Ythdf1 in dopamine D1- or D2 receptor-expressing neurons selectively impaired D1- or D2-dependent learning, respectively, including both adaptive and maladaptive learning. This highlights YTHDF1 as a potential therapeutic target for preventing pathological plasticity. YTHDF1 recognizes m 6 A modifications on transcripts and regulates their translation. Elevated cAMP triggered increased protein synthesis in control striatal neurons but not in Ythdf1 -deficient neurons. Behaviorally, cell-type-specific Ythdf1 deletion resembled learning phenotypes caused by deletion of the m 6 A methyltransferase gene Mettl14 , suggesting YTHDF1 as the main mediator of m 6 A-dependent regulation in the striatum.